(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study examines two contemporary approaches to language teaching and learning: Content-Based Learning (CBL) and Project-Based Learning (PBL). The research explores how these methodologies integrate language acquisition with meaningful content and authentic tasks, analyzing their theoretical foundations, implementation strategies, and effectiveness in various educational contexts.